Nicotinic Acetylcholine Receptor Agonists for the Treatment of Alzheimer's Dementia: An Update. Issue 3 (22nd August 2018) - Hoskin, Justin L; Al-Hasan, Yazan; Sabbagh, Marwan Noel
Abstract: : A significant portion of the clinical phenotype observed in Alzheimer's disease (AD) occurs through nicotinic acetylcholine receptors (nAChRs). Degeneration of cholinergic neurons, combined with aberrant nAChR expression and activation partially through amyloid-beta peptide (Aβ)–nAChR leads to upregulation of pro-inflammatory pathways and subsequently the progressive cognitive decline of AD. Interestingly, the cholinergic anti-inflammatory pathway is also mediated through nAChR particularly α7 nAChR. Thus, agonists of these receptors will likely exert pro-cognitive benefits through multiple mechanisms including stimulating the cholinergic pathway, modulating inflammation, and buffering the effects of amyloid. Despite this promising theoretical use, trials thus far have been complicated by adverse effects or minimal improvement. This review will provide an update on several pharmacological nAChR agonists tested in clinical trials and reasons that further investigation of nAChR agonists is merited. Implications: nAChRs have consistently presented a promising theoretical use in the treatment of AD; however, trials thus far have been complicated by adverse effects or minimal improvement. This review will provide an update on several pharmacological nAChR agonists trialed and reasons that further investigation of nAChR agonists is merited.